From worker to peasant and then to entrepreneur? Land reform and agrarian change in the Saïss (Morocco). (May 2018) - Petit, Olivier; Kuper, Marcel; Ameur, Fatah
Highlights: We analyze the emerging entrepreneurial practices on family farms in two former agrarian reform cooperatives in Morocco. We show the coexistence and hybridization of practices and logics pertaining to different modes of farming. Young farmers form nodal points in the multiple interactions between different modes of farming. Abstract: The aim of this paper is to analyze the emerging entrepreneurial practices on family farms in two agrarian reform cooperatives in Morocco. Their emergence can be explained by the constant negotiation of multiple and sometimes even antagonistic logics within these farms in a context of rapid agrarian change and the juxtaposition of capitalistic, entrepreneurial and peasant farms in the same area. Through their engagement as workers or sharecroppers in the different types of farms and as household members on the family farm, the young farmers from the dismantled agrarian cooperatives participate actively in the transformation of farming modes. The porosity of the peasant and entrepreneurial worlds is the main lesson we draw from our study. There is a subtle process of hybridization between the peasant and entrepreneurial modes of farming, resulting in a wide range of profiles. If we only focus on the political discourse, the trend towards capitalistic and entrepreneurial modes of farming seems inescapable. Nevertheless, our study stresses the resistance of peasant modes of farming that can blend with a 'modern' perception of agriculture.